Effectiveness of a short, intensive, art-based group intervention on attention level in children with autism spectrum disorders: a pre-post experimental study: Group art-based intervention and attention level in children with ASD - Abdulah, Deldar Morad; Abdulla, Bayar Mohammed Omar; Liamputtong, Pranee (Paediatrica Indonesiana, 2024)
Background The rate of autism spectrum disorder (ASD) is dramatically rising globally, especially in the Middle East and North Africa. There has been little research on the effects of art-based interventions on attention impairments among children with ASD. Objective To examine the effectiveness of a short, intensive, art-based intervention on attention switching and attention to detail in children with moderate-severe ASD. Methods In this pre- and post-experimental study, children previously diagnosed with levels 2 and 3 ASD were invited to join a one-month, art-based course. The art-based intervention was held 3 days/week for 2 hours per day. Results The mean age of subjects was 8.33 (range 5 to 11) years; there were 10 (83.33%) males and 2 (16.67%) females. The total Autism Spectrum Quotient (AQ-Child) scores from baseline to one week after completion of the art-based course were not significantly different. In addition, mean social skills scores of attention switching and attention to detail, as well as communication scores were not significantly changed from baseline to after course completion. However, the children had significantly worse median imagination scores after the course compared to baseline scores (18.0 vs. 16.0, respectively) (P=0.0020). Conclusion After a one-month, art-based, group intervention, AQ-Child scores did not change significantly in total score, social skills, attention switching, attention to detail, or communication. The median imagination score worsened after, compared to before, the intervention. However, these results need to be interpreted with caution due to the very small sample size.